(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The focus of this article is Holocaust education as well as the teaching and learning of race theories, as set out in the Curriculum and Assessment Policy Statements (CAPS) for Grade 9 Social Sciences (History), and Grade 11 History. The article makes general statements about aspects of this history, and possible methodological approaches, especially in areas which present a challenge: victimhood, resistance, historiography and interpretation, the phrasing of assessment questions, impartiality and neutrality, unpacking concepts and assumptions, conflation and fudging, race, role play, and independent learner research. There is specific focus on four of the textbooks used in the teaching of Grade 11 History; questions from these books are cited and discussed. The questions selected illustrate the difficulties commonly encountered in the teaching and learning of the Grade 11 “Theories of Race” component. The article draws on the contributions of various individuals and bodies to the teaching of difficult histories, and attempts to provide suggestions for an approach guided by rigorous analysis in the context of the human rights History classroom.